COMPLEX USAGE OF CLAY USED MATERIALS - Matvyeyeva, Olena; Bovsunovskyy, Eugene; Lapan, Oksana; Ryabchevsky, Oleg (Proceedings of National Aviation University (archive), 2016)
The article represents the results of research on the application of technological wastes of aerosol gasdynamic suspension treatment of aircraft elements for the heavy metal ions sorption from industrial wastewaters. Therecommendations on utilization of polluted sorbents by depositing in constructional materials are represented.